Effects of predictive nursing interventions on agitation during recovery period of general anesthesia in patients undergoing laparoscopic surgery - LI, Meng; WANG, Hairong; LIU, Xiaocan; MA, Yanli; XING, Xueyan (Chinese Journal of Integrative Nursing, 2025)
Objective To investigate the predictive nursing interventions on agitation during recovery period of general anesthesia in patients undergoing laparoscopic surgery. Methods A total of 164 patients undergoing general anesthesia for laparoscopic surgery were included as research objects, and they were divided into the control group (n=82)and study group (n=82). All patients received routine nursing management during the operation period, and those in the study group received predictive interventions on potential risk factors during the operation period. The Richmond Agitation-Sedation Scale (RASS) 15 minutes after operation, recovery time, incidence of emergence agitation, vital signs during recovery period and postoperative recovery index were compared between two groups. Results The RASS score of patients in the study group was lower than that of patient in the control group (P＜0. 05). The incidence of emergence agitation in the study group was lower than that in the control group(P＜0. 05). The range of changes in systolic blood pressure, diastolic blood pressure, heart rate and body temperature in the study group were small compared with those in the control group(P＜0. 01). The recovery time, time to spontaneous breathing recovery and extubation time in the study group were shorter than those in the control group(P＜0. 01). Conclusion The predictive nursing intervention is effective to shorten the recovery time, reduce the incidence of emergence agitation and help to maintain the stable vital signs during the operation period. (目的 探讨围术期护理干预对腹腔镜手术患者全身麻醉苏醒期躁动的影响。方法 选取2023年1月—7月医院收治的行全身麻醉腹腔镜手术患者164 例为研究对象, 分为对照组(n=82)和研究组(n=82)。对照组采用常规围手术期护理干预, 研究组在对照组基础上采用预见性护理干预措施。对比两组术后15 min RASS镇静评分、苏醒时间、苏醒期躁动发生率、苏醒期生命体征和术后恢复相关指标。结果 研究组患者术后15 min RASS评分低于对照组(P＜0. 05)。 研究组苏醒期躁动发生率低于对照组, 差异有统计学意义(P＜0. 05)。麻醉苏醒期, 研究组收缩压(SBP)、舒张压(DBP)、心率(HR)升高幅度较对照组小, 体温(T)降低幅度较对照组小, 差异有统计学意义(P＜0. 01)。与对照组相比, 研究组麻醉苏醒时间、自主呼吸恢复时间和拔管时间缩短, 差异有统计学意义(P＜0. 01)。结论 围手术期预见性护理干预措施可缩短腹腔镜手术患者全身麻醉苏醒时间, 降低苏醒期躁动发生率, 维持生命体征平稳。)